Cancer Incidence in Elderly Medicare and Dually Eligible Beneficiaries - Bradley, Cathy J (Blackwell Science Inc, 2008)
OBJECTIVE: We assessed how Medicaid enrollment and race influence cancer incidence among patients age 65 years and older. DATA SOURCES AND METHOD: Population-based Michigan Tumor Registry was merged with Medicaid eligibility files for 1996 through 2000. All analyses were age-adjusted and gender-specific. We compared cancer incidence in the elderly Medicaid population to the cancer incidence in the Medicare population. We then examined cancer incidence in patients continuously enrolled in Medicaid 12 or more months relative to the incidence in the Medicare population. PRINCIPAL FINDINGS: When comparing cancer incidence in Medicaid patients without regard to enrollment before diagnosis, the incidence rates of prostate cancer in black men and colorectal cancer in black women were statistically higher relative to the incidence rates in white patients. The overall cancer incidence rate for all cancers combined was statistically significantly higher for black women and men compared with white women and men (incidence rate ratio=1.18 and 1.48, 95 percent confidence interval 1.05–1.32 and 1.28–1.71, respectively). In dually eligible patients enrolled 12 or more months before diagnosis, an excess cancer incident was observed for black patients relative to white patients in every cancer site examined with the exception of lung cancer. CONCLUSIONS: Medicaid data in addition to Medicare data revealed patterns of cancer incidence that varied according to Medicaid enrollment and race. These findings suggest that the cancer burden among African Americans and dually eligible patients is substantial.